Amobilisasi Inulinase Aspergillus clavatus Gmn 11.3 Galur Lokal Indonesia dengan Matrik Karbon Aktif - Saryono, Saryono; R.M, Henny Olivia; Sepriana, Elvita; Dahliati, Andi; A.M, Chainulfiffah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2007)
Two types of inulinase are produced by Aspergillus clavatus Gmn 11.3 within the 3rd and 5th days of fermentation. The optimum condition of two types of immobilized inulinase is achieved using 20 grams of activated carbon, 200 meshes with protein adsorption of 96.71% and 96.19% respectively. Following immobilization of inulinase, incubation was carried out for 30 hours to hydrolyze inulin. After incubation, the proteins retained on the matrix are 66.96% of the 3 days fermentation enzymes and 37.36% for 5 days of fermentation enzyme.